Short communicationA cockscomb-like aneurysm of the right coronary artery after bare metal stent implantation - Kalkan, Mehmet Emin; Açar, Göksel; Mustafa Tabakcı, Mehmet; Demir, Serdar; Sahin, Müslüm; Akçakoyun, Mustafa (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Coronary artery aneurysm (CAA) formation is an uncommon but potentially life-threatening event after coronary balloon angioplasty or stent implantation. In this report, we present a case of a patient who had a cockscomb-like aneurysm after bare metal stent implantation which was successfully treated with a coronary graft stent.